Complementarity of International Instruments in the Field of Biosecurity - Iris M. Vennis; Iris M. Vennis; Maja Boskovic; Diederik A. Bleijs; Saskia A. Rutjes; Saskia A. Rutjes (Frontiers Media S.A., 2022)
The COVID-19 pandemic has demonstrated the devastating impact of infectious disease outbreaks and the threat of emerging and re-emerging dangerous pathogens, independent of their origin. Natural, accidental, and deliberate disease outbreaks all need systems in place for an effective public health response. The best known international instrument in the field of public health is the WHO International Health Regulations (2005). Although the International Health Regulations are mainly focused on natural disease outbreaks, the actions to take to comply with them also contribute to biosecurity and non-proliferation. This paper examines in case of full implementation of the International Health Regulations, what other actions states should take to comply with international biosecurity instruments, including the Biological and Toxin Weapons Convention and United Nations Security Council Resolution 1540, to effectively prevent and defend against intentional biological threats. An overview of international instruments from different disciplines regarding biosecurity is presented. Furthermore, this paper clarifies the similarities between the international biosecurity instruments and addresses the additional requirements that instruments stipulate. From a detailed comparison between the instruments it can be concluded that, to adhere to all legally-binding international biosecurity instruments, specific non-proliferation and export control measures are necessary in addition to full implementation of the International Health Regulations. Additionally, an overview of non-legally binding instruments in the field of biosecurity is presented and practical implementation examples are highlighted. Compliance with legally binding instruments can be improved by precise guidance provided by non-legally binding instruments that are clear and attuned to the situation on the ground. To improve understanding of the existing international instruments, this paper aims to provide an overview of the international legal biosecurity framework to biosecurity experts, policymakers, civil servants, and practitioners. It offers possible practical applications for the politico-legal context and accommodates the enhancement of full employment of biosecurity resources for an improved multidisciplinary capacity to prevent, detect, and respond to infectious disease outbreaks.